An analysis of the effectiveness of Restoration of Family Links (RFL) to African refugees by the Red Cross in Zimbabwe: the case of Tongogara Refugee Camp - Chuma, Forgive (Midlands State University, 2015)
The global village has seen a significant margin of persons who are not living in their countries of origin but somewhere beyond their national borders as refuges. Therefore this study sought to analyze the effectiveness of Restoration of Family Links (RFL) to African refugees and the case study was Tongogara refugee camp in Zimbabwe. The research revealed that restoration of family links improves displaced persons in issues of health, performance and behavior. In the same vein, relations between the source countries of refugees and the receiving countries are improved. Manifold causes of displacement of citizens and/or displacement of the displaced persons were delved on. Despite the challenges, RFL has been a program recommended by recipients under study, other humanitarian organizations as well as the researcher. The research relied on interviews and observation as research instruments. Recommendations were given at the end of the study for policy formulation and implementation as well as to improve service delivery both to the sending and receiving country.